A Comparison of Organic Cement Made from Recycled Waste Material and Portland Cement - Syarif, M.; Tjaronge, M. W. (Engineering, Technology & Applied Science Research, 2021)
Organic cement is an environmentally friendly alternative to Portland cement which is acquired by recycled organic waste and Mediterranean soil. Waste management is a global problem. The physical characteristic test results of the organic cement show that the weight test of fresh organic concrete is 2081kg/m³ and the dry weight of concrete is 2032kg/m³ which are smaller than Portland cement concrete’s which are 2525kg/m³ and 2405 kg/m³ respectively. The fineness of alternative cement grains that passed the 200 mesh sieve is 56%, which is more than Portland cement’s which is 52%. The solid weight of alternative cement is 1200kg/m3 whereas the solid weight of Portland cement is 1250kg/m3.